Hepatectomy With Portal Vein Resection for Hilar Cholangiocarcinoma: Audit of 52 Consecutive Cases - Ebata, Tomoki (2003)
OBJECTIVE: To better determine the role of portal vein resection and its effect on survival, as well as to appreciate the impact of portal vein invasion on prognosis in hilar cholangiocarcinoma. SUMMARY BACKGROUND DATA: Hepatectomy with portal vein resection is sometimes performed for locally advanced hilar cholangiocarcinoma. However, the significance of microscopic invasion of the portal vein has not been determined. METHODS: Medical records of 160 patients with hilar cholangiocarcinoma who underwent macroscopically curative hepatectomy with (n = 52) or without portal vein resection (n = 108) were reviewed. Invasion of the portal vein was assessed histologically on the surgical specimen, and results were correlated with clinicopathologic features and survival. RESULTS: Surgical mortality, including all hospital deaths, was similar in patients who did and did not undergo portal vein resection (9.6% vs. 9.3%), but the primary tumor was more advanced in patients who underwent portal vein resection. Histologically, no invasion was found in 16 (30.8%) of resected portal veins. However, dense fibrosis adjacent to the portal vein was common, and the mean distance between the leading edge of cancer cells and the adventitia of the portal vein was 437 ± 431 μm. The prognosis was worse in patients with than without portal vein resection (5-year survival, 9.9% vs. 36.8%; P < 0.0001). The presence or absence of microscopic invasion of the resected portal vein did not influence survival (16.6 months in patients with microscopic invasion vs. 19.4 months in those without; P = 0.1506). Multivariate analysis identified histologic differentiation, lymph node metastasis, and macroscopic portal vein invasion as independent prognostic factors. CONCLUSIONS: Microscopic invasion of the portal vein may be misdiagnosed clinically in patients with hilar cholangiocarcinoma. However, the distance between tumor and adventitia is so narrow that curative resection without portal vein resection is unlikely to be possible. Gross portal vein invasion has a negative impact on survival, and hepatectomy with portal vein resection can offer long-term survival in some patients with advanced hilar cholangiocarcinoma.